PWO based electromagnetic calorimetry to operate at a low temperature - Orsich, Pavel O.; Brinkmann, Kai-Thomas; Dormenev, Valery I.; Korzhik, Mikhail V.; Mechinsky, Vitaly A.; Kozlov, Dmitry Yu.; Zaunick, Hans-Georg (Journal of the Belarusian State University. Physics, 2021)
The degradation of the optical transmittance under ionising radiation of the scintillation crystal in the scintillation spectral range leads to the losses of the light output, which results in the deterioration of the energy resolution and limits the operation time of the calorimeter made of the scintillator. This effect is especially prominent for calorimeters operating at a low temperature. The use of a lead tungstate scintillation crystal PbWO4 in calorimetry at a low temperature in the range from –20 to –45 °C provides a threefold increase in its scintillation yield, which causes a significant improvement in the energy resolution in the range up to 10 MeV. Keep on this feature is critically important for hadron spectroscopy. However, as the temperature of the PbWO4 crystal is lowered, the rate of spontaneous relaxation of colour centers created under ionising radiation significantly slows down, which shifts the dynamic level of the induced absorption towards a higher value under long-term irradiation of high-energy physics experiments. A comparison is made of the spontaneous relaxation of induced absorption in the spectral region of scintillations with stimulated relaxation upon irradiation of samples by infrared photons of different wavelengths. It is shown that the relaxation of colour centers can be accelerated up to one thousand times. Thus, recovery stimulation allows fast and efficient in situ recovery of the crystal optical transmittance either at beam-off periods or online at data acquisition. The application can substantially improve or extend the running period of the PWO based calorimeters at low temperatures by keeping the radiation damage at a tolerable level.